Նորից Խորենացու Աոաջին Արտաշեսի մասին - Մուրադ Օհանյան (ՀՀ ԳԱԱ հրատ.)
Многие исследователи, считая образ Первого Арташеса у Мовсеса Хоренаци откликом на народные предания, видели в нем дела Митридата VI Понтийского и Тиграна Великого. Но этот образ создан на совместимых достоверных исторических данных. Существенная часть этих данных — и основной общностью, и редкими своеобразными деталями — полностью приводит к определенному историческому лицу — властителю Армении, затем царю - царей Ахеменидской державы — Дарию III Кодоману.Many researchers consider the image of the First Artashes of Movses Khorenatsi to be an echo of historical and national memoirs. Specifically, they see it as reflecting Mithradates VI and Tigranes The Great. But the image, which I have briefly addressed in the past, is rooted in historical data. That data, generally, as well as in its specific and unique details, reveals the image to be that of a historical person, - previously the satrap of Armenia, and then the king of the kings of Achaemenian Empire - Darius III Codommanus.
Keywords: History; Ancient History; D History